Integrating Different Types of Knowledge to Understand Temporal Changes in Reef Landscapes - Quirino-Amador, Maria Iohara; Longo, Guilherme Ortigara; Freire, Fúlvio Aurélio de Morais; Lopes, Priscila F. M. (Frontiers in Ecology and Evolution, 2021)
Reefs are highly diverse ecosystems threatened by anthropogenic actions that change their structure and dynamics. Many of these changes have been witnessed by different reef users who hold specific knowledge about the reefscape according to their experiences and uses. We aimed to understand whether fishers, divers, and reef scientists have different perceptions of general changes that have occurred in reefs and whether their knowledge converge, diverge or are complementary. We conducted 172 semi-structured interviews with stakeholders from Northeast and Southeast Brazil where either coral or rocky reefs occur, comprising most reefs occurring in the Southwestern Atlantic Ocean. Reef scientists and divers perceived corals have undergone the sharpest declines among reef species and indicate pollution and tourism as the major negative impacts on reefs. On the contrary, fishers noticed greater declines in fishing targets (i.e., groupers) and have hardly noticed differences in coral abundance or diversity over time. Divers had a broader view of changes in reef organisms, with some level of convergence with both reef scientists and fishers, while reef scientists and fishers provided information on more specific groups and economically relevant resources, respectively. The different stakeholders generally agree that reefscapes have undergone negative changes including diversity loss and abundance declines of reef organisms. The complementarity of information among different stakeholders enables a better understanding of how human behavior impact and perceive changes in natural ecosystems, which could be essential to manage reef environments, particularly those without baseline data.